Economic impacts of electricity transmission and distribution losses in Pakistan: A dynamic inoperability input–output analysis - Ayesha Hidayat Ullah; Yousaf Ali; Muhammad Sabir (Utilities Policy, 2026)

Enhancing ionic conduction through surface incorporation of wide bandgap material into perovskite for low temperature ceramic fuel cells (LT-CFCs) - Xiuli Bai; Fei Wang; M.A.K. Yousaf Shah; Haijun Wang; Lian Chen; Muhammad Imran; Yuzheng Lu (Fuel, 2026)

Airborne dust particle-induced lung inflammation in mice alleviated by adipose stem cell-derived conditioned medium - Hazrat Zaman; Madiha Habib; Zobia Safdar; Shafi Zaman; Hafiza Sumbul Yousaf; Muhammad Shahbaz Aslam; Zaigham Abbas (Aerobiologia, 2026)

Adaptive strategies of Tamarix aphylla in hyper-saline conditions of Cholistan Desert - Muhammad Akram; Nargis Naz; Hafiz Muhammad Mohsin Hassan; Maqbool Ahmed; Leman Aliyeva; Muhammad Yousaf Nadeem; Hind Saad Alsubaie; Sahar Anwar Almalki; Abdelrahman R. Ahmed; Abdullah R. Alanzi (The Science of Nature, 2026)

Interfacial Stabilization and Geochemical Transformation of Antimony in Contaminated Soil Using a Ferrihydrite-Functionalized Biochar–Montmorillonite Composite - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Samra Ijaz; Ruijia Liu (International Journal of Environmental Research, 2026)

Integrating skill-based weighting and probabilistic modeling for enhanced drought index construction from GCM outputs - Mahrukh Yousaf; Zulfiqar Ali; Farman Ali; Hussnain Abbas; Sadia Qamar; Muhammad Mohsin (Meteorology and Atmospheric Physics, 2026)

Gas separation in industrial bulk chemistry and relevance for transitioning to industrial plasma chemistry - Volker Hessel; Nguyen Van Duc Long; Marc Escriba-Gelonch; Jose Osorio Tejada; Muhammad Yousaf Arshad; Anubhav Sabharwal; Gabriele Centi; Annemie Bogaerts; Evgeny Rebrov; Peter H. Seeberger (Chemical Engineering Journal, 2026)

Engineered Adsorbents for Microplastic Mitigation: From Interfacial Mechanisms to Scalable Environmental Perspectives - Hammad Sajjad; Waleed Altaf; Ramika Javaid; Tehreem Fakhra; Muhammad Hayat; Ammar bin Yousaf; Nadeem Raza; Suryyia Manzoor; Lilia Basilio de Caland (Journal of Environmental Chemical Engineering, 2026)

Retraction notice to “Does communicable diseases (including COVID-19) may increase global poverty risk? A cloud on the horizon” [Environ. Res. 187 (2020) 109668] - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Xuan Vinh Vo; Khalid Zaman (Environmental Research, 2026)

First molecular record of Panaeolus subbalteatus (Psathyrellaceae, Agaricales) from Pakistan - Saliha Rukhsar; Nousheen Yousaf; Sadaf; Mahneem Fazal; Muhammad Hanif; Murad Muhammad; Dilfuza Egamberdieva; Wen-Jun Li (Antonie van Leeuwenhoek, 2026)

Genetic Ranking of Potato Varieties is Different in Scandinavian and Mediterranean Environments - Muhammad Farhan Yousaf; Hélène Romé; Merethe Bagge; Mathias Timmermann; Just Jensen; Thinh Tuan Chu (American Journal of Potato Research, 2026)
Understanding genotype-by-environment interaction (G×E) is essential for breeding potato cultivars adapted to different regions. We analyzed ~ 13,000 tetraploid breeding lines evaluated over 17 years in Denmark (DK), Spain (ES), and Morocco (MO), representing Scandinavian and Mediterranean mega-environments. A pedigree-based mixed model was fitted for yield, tuber size, and resistance towards scab. Significant G×E was detected for yield and scab, evidenced by lack of unit genetic correlations between environments, heterogeneous genetic variances, and differing heritabilities. Additive genetic correlations for yield were 0.54 (DK–ES), 0.64 (DK–MO), and 0.78 (ES–MO); scab correlation between DK and ES&MO was 0.6. Yield genetic variance in ES was more than twice compared with DK and MO, whereas scab variance was higher in DK. Tuber size showed weaker G×E (r a = 0.82). Within mega-environments, genotype × environment components explained 16.8–26.9% of yield variance. Results indicate substantial re-ranking of breeding values; therefore, environment-specific prediction is recommended.

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Tailoring SrFeO3-δ cathodes via Nd and Cu doping for boosting ORR activity for high-performance LT-PCFCs below 600 °C - Naveed Mushtaq; Wu Ping; Badriah S. Almutairi; Sajid Rauf; M.A.K Yousaf Shah; Muhammad Sultan Irshad (Fuel, 2026)

Forecasting earthquake recurrence with long-term fault memory and variable stress release: insights from the Main Himalayan Thrust - Muhammad Yousaf Khan; Fabrice Cotton; Danijel Schorlemmer; Talat Iqbal (Stochastic Environmental Research and Risk Assessment, 2026)

Exogenous Allantoin Attenuates Cadmium-Induced Toxicity in Rapeseed via Reducing Cd Accumulation and Modulating Antioxidant Defense Systems - Wenqiang Lan; Skhawat Ali; Mengting Lyu; Basharat Ali; Yiwa Hu; Muhammad Arslan Yousaf; Di He; Juanjuan Li; Yingying Zhou; Weijun Zhou (Journal of Plant Growth Regulation, 2026)

Parametric optimization and mechanistic investigation of polyvinyl chloride microplastic degradation via an intensified hydrothermal Fenton reaction - Muhammad Zeeshan Gulzar; Guijian Liu; Muhammad Imran; Muhammad Arif; Samina Irshad; Bisma Sattar; Muhammad Irtaza Sajjad Haider; Huihui Zhou; Balal Yousaf (Journal of Water Process Engineering, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Bioactive phenolic allelochemicals from mulberry leaf litter through bioassay-guided fractionation and their bioherbicidal activity - Shagufta Perveen; Muhammad Naeem Mushtaq; Muhammad Yousaf; Raihan Ismil (Natural Product Research, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Structural characterization of exopolysaccharide from Lacticaseibacillus rhamnosus and its protective mechanism against dyslipidemia in obese mice - Qinqin Li; Lingxing Feng; Muhammad Yousaf; Dongmei Liu (Food Bioscience, 2026)

Retraction notice to ‘Morpho-chemical characterization and source apportionment of potentially toxic metal(oid)s from school dust of second largest populous city of Pakistan’ [Environ. Res. 196 (2021) 110427] - Abdul Rehman; Guijian Liu; Balal Yousaf; Rafay Ahmed; Muhammad Saqib Rashid; Samina Irshad; Awais Shakoor; Muhammad Raza Farooq (Environmental Research, 2026)

Synergistic photo-assisted AOPs using acid-modified biochar: Enhanced micropollutant levofloxacin degradation in industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Bisma Sattar; Muhammad Zeeshan Gulzar; Hameer Chand; Ruijia Liu (Desalination, 2026)

Photo-activated defect engineering unlocks high-performance proton transport in garnet electrolytes - Bushra Bibi; Atif Nazar; Muhammad Yousaf; Tanveer Farid; Rizwan Raza; Syed Asad Abbas Bukhari; Muhammad Faisal Anawar; Kashif Nazar; Hafsa Mansha; Yuzheng Lu; Bin Zhu (Chemical Engineering Journal, 2026)

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Molecular Identification and Phylogenetic Analysis of Lumpy Skin Disease Virus-P32 Gene in Cattle of Potohar Region, Pakistan - Gohar Khadim; Aamer Ali Shah; Aayesha Riaz; Mian Muhammad Awais; Arfan Yousaf; Mahwish Ali; Bakhtawar Khadim; Nimra Riaz (Current Microbiology, 2026)

Advances in fulvic acid extraction from lignite: techniques, challenges, and applications - Iqra Yousaf; Lizhen Gao; Iffat Riaz; Sidra Pervaiz; Muhammad Usman (Environmental Monitoring and Assessment, 2026)

Advancements in heterostructure electrolytes for Low-Temperature SOFCs, and the role of insulating a-Al2O3 in BaCe0.7Zr0.1Y0.1Yb0.1O3-δ-Based composites - Yuzheng Lu; Wenyu Li; Muhammad Khalid; M. A. K. Yousaf Shah; Chunhua Lu (Fuel, 2026)

Development of co-integrated standardized procedure for the joint monitoring, forecasting and probabilistic characterization of climate extremes under global climate models - Aamina Batool; Mahrukh Yousaf; Muhammad Shakeel; Amina Magdich; Reem Alreshidi; Zulfiqar Ali; Veysi Kartal (Theoretical and Applied Climatology, 2026)

Improving growth and physicobiochemical attributes of rice via PGR-based seed priming: a comparative study of establishment methods - Yousaf Saeed; Muhammad Aurangzaib; Hossam S. El-Beltagi; Khairiah Mubarak Alwutayd; Ghulam Murtaza; Lala Gurbanova; Rashid Iqbal (Cereal Research Communications, 2026)

Hydrogeochemical dynamics of sub-Himalayan springs: assessing health risks and environmental impacts in Muzaffarabad, Pakistan - Mansoor Awan; Abrar Niaz; Ahmer Bilal; Muhammad Saleem Mughal; Li Yang; Xingyue Qu; Ali Yousaf Khan (Carbonates and Evaporites, 2026)

Overcoming global climate model inconsistencies in drought projection with the development of dual divergence correlation weighting scheme over Pakistan - Mahrukh Yousaf; Amara Farooq; Sadia Qamar; Naim Ahmad; Muhammad Shakeel; Aamina Batool; Zulfiqar Ali; Veysi Kartal (Acta Geophysica, 2026)

Radon concentration, its deterministic and probabilistic health risks through groundwater consumption, and spatial distribution - Said Muhammad; Fawad Hussain; Saeeda Yousaf; Zafar Iqbal; Umar Farooq; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Novel Styrofoam-sludge biochar for Pb and Zn adsorption: Bioavailability and reduction in maize-cultivated contaminated soils - Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Ruilian Yu; Gongren Hu; Balal Yousaf; Sajid Ali; Muhammad Adnan; Cheng Liping; Xiangliang Pan; Ming Hung Wong (Journal of Cleaner Production, 2026)

Investigation of photocatalytic efficiency and antimicrobial activity via Mn doped SnO2 using an eco-friendly green synthesis method - Laraib Bibi; Tahir Iqbal; Mariam Seemab; Sumera Afsheen; I.M. Ashraf; Faiza Saeed; Atif Mossad Ali; Muhammad Yousaf; M.A. Sayed (Journal of Environmental Chemical Engineering, 2026)

Synergistic role of microbes and wetland plants in an advanced-acclimatized constructed wetland for enhanced removal of heavy metals - Adnan Abbas; Muhammad Ahmad; Maryam Yousaf; Linghui Pan; Dayong Xu (Gondwana Research, 2026)

Disordered Pr-alumina: Enabling fast proton dynamics across energy systems - Hafsa Mansha; Touseef Ahmad; Kashf Zaman; Sajid Rauf; Muhammad Khalid; M.Ahsan Masood; Shahzad Rasool; Atif Nazar; Bushra Bibi; Nawal K. Almaymoni; Yuzheng Lu; Jun Wang; et al. (Fuel, 2026)

Functional hydrogels—enabling the gateway for sustainable water treatment and harvesting technologies - Muhammad Shajih Zafar; Marco Vocciante; Johan Bobacka; Muhammad Nadeem Asghar; Muhammad Yousaf; Henrik Grénman (Environmental Research, 2026)

Integrated assessment of groundwater potential and quality in a seismically active Himalayan city: a case study from Muzaffarabad, Pakistan - Raja Dilawar Sajjad; Abrar Niaz; Ahmer Bilal; Muhammad Tayyib Riaz; Ali Yousaf Khan; Xiwu Luan (Environmental Geochemistry and Health, 2026)

Inter-fuel substitution management and carbon mitigation in Saudi Arabia: Evidence based on carbon neutrality plan 2060 - Guangwei Zhang; Muhammad Yousaf Raza (Journal of Environmental Management, 2025)

A functional self-assembled layer with preferential sodium adsorption sites for ultra-stable sodium metal batteries - Moazzam Ali; Asif Mahmood; Muhammad Ali; Samia Aman; Hamid Hussain; Xuan Zhang; Yinzhu Jiang; Xufeng Lin; Muhammad Yousaf (Chemical Engineering Journal, 2025)

Crustal stress redistribution and aftershock patterns in the Northwestern Himalaya following the 2019 Mirpur earthquake - Mohammad Tahir; Muhammad Yousaf Khan; Seema Tahir; Talat Iqbal (Journal of Seismology, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

Heavy metals contamination of roadside dust, risk assessment, and their spatial distribution along the M-1 motorway - Sehrish Amin; Wajid Ali; Said Muhammad; Saeeda Yousaf; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Surface defect engineering of perovskite oxide towards CO2 tolerant cathode in solid oxide fuel cells - Meinfeng Wu; Muhammad Yousaf; Haohui Song; Jiquan Deng; Yang Liu; Jing Shao; Youkun Tao (Fuel, 2025)

Multivalent metal-ions intercalation for enhanced structural stability and pseudocapacitance in titanium carbonitride (Ti₃CNTₓ) MXenes for asymmetric supercapacitor applications - Sheryar Abid; Aiza Kanwal; Muhammad Zubair Iqbal; Muhammad Yousaf; Asif Mahmood; Syed Rizwan (Chemical Engineering Journal, 2025)

High-performance clay and K2CO3-Modified sludge biochar for efficient reactive black-5 Removal: Mechanistic insights and alleviation of phytotoxicity - Muhammad Arif; Guijian Liu; Muhammad Zia-ur-Rehman; Qumber Abbas; Aniqa Ashraf; Muhammad Saqib Rashid; Krzysztof Pikon; Balal Yousaf (Biomass and Bioenergy, 2025)

Sustainable biodiesel production from non-food biomass of Cucumis prophetarum via waste peel-based phyto-nanocomposite in membrane reactor: An innovative outlay for waste management and circular bioeconomy - Maria Ameen; Mushtaq Ahmad; Muhammad Zafar; Balal Yousaf; Muhammad Faisal Amin; Iftikhar Ahmed; Shabir Ahmad (Biomass and Bioenergy, 2025)

Characterization of ambient air quality and its relationship with respiratory morbidity in typical cities of Northwest China (NWC) - Shah Zaib; Jianjiang Lu; Gao Yan; Xiaowen Yin; Xiaoning Lei; Muhammad Zeeshaan Shahid; Azhar Siddique; Mariam A. Yousaf Al-Nesf (Air Quality, Atmosphere & Health, 2025)

How likely are high schools to adopt vegetable gardens to combat food insecurity? - Ayesha Noor Fatima; Khurram Yousaf; Muhammad Waqas Alam Chattha (Environment, Development and Sustainability, 2025)

Leveraging immunoinformatic for the rational design of highly immunogenic multi-epitope subunit vaccines against Dugbe virus: a molecular docking and simulation approach - Ali khan; Safir Ullah Khan; Fazal Akbar; Fakhrul Hassan; Zafar Ali; Haji Khan; Shahid Ali; Muhammad Yousaf; Hadi M. Yassine; Sergio Crovella; Muhammad Suleman (In Silico Pharmacology, 2025)

Functionalized biochar with enhanced interfacial properties for synergistic adsorption and photodegradation mechanisms of levofloxacin in industrial effluents - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Ruijia Liu (Process Safety and Environmental Protection, 2025)

Waste to wonder: Sustainable photocatalytic biochar from agro-plastic waste for advanced wastewater treatment - Muhammad Ahmad; Maryam Yousaf (Journal of Environmental Chemical Engineering, 2025)

Kaempferol alleviates cypermethrin induced reproductive toxicity in rats via Nrf2-mediated antioxidant and apoptotic regulation with histopathological evidence: in vivo and in silico study - Fahad Kabeer; Shaista Anjum; Atique Ahmed Behan; Muhammad Usman; Nazima Yousaf khan; Muhammad Azeem; Hafiz Misbah Ud Din; Muhammad Adeel Arshad; Sadaf Nazir; Shiping Cheng; Jameel Ahmed Buzdar (Journal of Molecular Histology, 2025)

Comparative Analysis of the Efficiencies of Two Low Cost Adsorbents for Carbon Dioxide Capture - Sayyaf Yousaf; Haris Abdullah Noor; Muhammad Wajid Ullah; Alireza Noorpoor; Adnan Ahmad Tahir; Maria Siddique; Romana Khan (International Journal of Environmental Research, 2025)

A novel Bi-weight Mid Correlation Coefficient Divergence (BMCCD) approach for multi-model ensemble-based drought assessment - Mahrukh Yousaf; Laraib Shafique; Sadia Qamar; Muhammad Shakeel; Farman Ali; Zulfiqar Ali (Environmental Monitoring and Assessment, 2025)

Corrigendum to “Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction” [363 (2024) 130919] - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2025)

Epidemiology of Lumpy Skin Disease virus in large ruminants of Potohar region, Pakistan - Gohar Khadim; Aamer A. Shah; Aayesha Riaz; Arfan Yousaf; Mahwish Ali; Mian Muhammad Awais; Muhammad Arif Zafar; Bakhtawar Khadim; Nimra Riaz (Tropical Animal Health and Production, 2025)

Mitigating Terminal Drought in Chickpea (Cicer arietinum L.) Using Organic Manures; Effects on Yield, Potassium Uptake and Antioxidants Activity - Malik Muhammad Yousaf; Azra Yasmeen; Shadia Hama Salih Kareem; Muhammad Arif; Hesham F. Alharby; Hameed Alsamadany; Yahya M. Alzahrani; Amnah M. Alamri; Ammara Latif; Hafeez ur Rehman (International Journal of Plant Production, 2025)

Development of RT-LAMP assay for variants of HCV in Pakistan - Zilwa Mumtaz; Sharmeen Saqib; Muhammad Zubair Yousaf; Muhammad Farhan Ul Haque (Brazilian Journal of Microbiology, 2025)

Investigating the development and success of Spodoptera Frugiperda (Lepidoptera: Noctuidae) on various wheat varieties: an age-stage specific life table analysis - Hamza Latif; Muhammad Arshad; Muhammad Irfan Ullah; Gulfam Yousaf; Nahdia Perveen; Wafa Abdullah Hamad Alkherb; Mohammed Ali Alshehri; Samy M. Sayed (International Journal of Tropical Insect Science, 2025)

Microplastic contamination in agricultural soils from mulch films and organic amendments: Transformation mechanism, soil-Biota toxicity, and future perspectives - Bisma Sattar; Guijian Liu; Balal Yousaf; Muhammad Arif; Muhammad Zeeshan Gulzar; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Samra Ijaz; Muhammad Awais Haider; Kiran Aziz (Waste Management, 2025)

Carbon nanotubes oriented bifunctional electrocatalyst supported on flexible material for overall water splitting - Alizah Jabeen; Ahmed M. Fallatah; Tahani Rahil Aldhafeeri; A. Alhadhrami; Abdulraheem SA Almalki; Sheraz Yousaf; Zeinhom M. El-Bahy; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2025)

Development of a Novel Multi-Model Ensemble Weighting Scheme for Improved Drought Assessment - Mahrukh Yousaf; Ali Iqbal; Sadia Qamar; Muhammad Shakeel; Maryam Ilyas; Zulfiqar Ali; Rizwan Niaz (Water Conservation Science and Engineering, 2025)

Adaptive responses of trees to industrial pollution: modulation of leaf anatomical, physio-biochemical, and heavy metal accumulation traits in urban biotopes - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Mansoor Javaid; Usman Zulfiqar; Nafosat Djonibekova; Anarjan Matkarimova; Hesham S. Almoallim; Mohammad Javed; Shafeeq Ur Rahman (Environmental Monitoring and Assessment, 2025)

Co-conversion of CO2 and refractory organics into bioplastics through a stable biocarrier - Muhammad Ahmad; Maryam Yousaf (Water Research, 2025)

Exploring single-atom catalysis for hydrogen evolution and storage: A DFT insight into first-row transition metal-porphyrin complexes (Porph@TMs) - Faheem Abbas; Saleem Nawaz Khan; Sadaf Bibi; Mariyum Yousaf; Francis Enujekwu; Muhammad Salman Khan; Sami Ullah; Mohammed Ali Assiri (Gas Science and Engineering, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Subsurface placement of controlled-release blended fertilizers mitigates ammonia volatilization by promoting nitrogen transformation in rice fields - Sajjad Ahmad; Muhammad Yousaf Nadeem; Shen Gao; Quanxin Li; Yanfeng Ding; Zhenghui Liu; Yu Jiang; Weiwei Li; Ganghua Li (Agriculture, Ecosystems & Environment, 2025)

Urban flood management from the lens of social media data using machine learning algorithms - Muhammad Waseem Boota; Shan-e-hyder Soomro; Jikun Xu; Muhammad Irshad Ahmad; Haoming Xia; Yaochen Qin; Muhammad Bilal Idrees; Naseem Ahmad; Chaode Yan; Ayesha Yousaf; Xiaoju Ning (Journal of Hydrology, 2025)

Transdermal Co-Delivery of Sumatriptan Succinate and Naproxen Sodium via Dissolving Microneedle Patch - Azka Yousaf; Zulcaif Ahmad; Asif Mahmood; Muhammad Imran Khan; Muhammad Furqan Akhtar (Journal of Pharmaceutical Innovation, 2025)

Comprehensive Genomic, Mutation, Phylogenetic, and Statistical Analysis of the Monkeypox Virus Across Multiple Countries - Imran Zafar; Faheem kanwal; Muhammad Azmat; Ahsanullah Unar; Ijaz Ali; Waqas Yousaf; Qurat ul Ain; Mohd Ashraf Rather; Nemat Ali; Mohammad Rashid Khan; Amandeep Singh Dhanju; Rohit Sharma (Indian Journal of Microbiology, 2025)

Physicochemical, Enzymatic, and Microbial Responses to Phosphofructokinase Overexpressing Transgenic Potato Cultivation: A Pot Experiment - Muhammad Junaid Sadiq Gill; Umer Ali; Aqib Hassan Ali Khan; Ismat Nawaz; Tayyab Ashfaq Butt; Cyrus Raza Mirza; Ameena Iqbal; Arfan Ali; Faiz Ur Rahman; Sohail Yousaf; Mazhar Iqbal (American Journal of Potato Research, 2025)

Organic matter and microplastics nexus: A comprehensive understanding of the synergistic impact on soil health - Samra Ijaz; Guijian Liu; Abdul Rehman; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Bisma Sattar; Muhammad Zeeshan Gulzar; Sofia Nosheen; Balal Yousaf (Science of The Total Environment, 2025)

Optical soliton solutions of the coupled equation in a stratified deep sea environment with engineering application - Naila Nasreen; Muhammad Abdaal Bin Iqbal; Muhammad Zubair Raza; Muhammad Yousaf; Zhaoliang Jiang (Ocean Engineering, 2025)

Hydrothermal integrated chemical treatment of microplastics for efficient degradation: Mechanistic insight and degradation behavior - Muhammad Zeeshan Gulzar; Guijian Liu; Balal Yousaf; Muhammad Imran; Muhammad Arif; Muhammad Nauman; Muhammad Irtaza Sajjad Haider; Bisma Sattar; Rabia Safeer; Samra Ijaz; Ruijia Liu (Journal of Water Process Engineering, 2025)

From waste to resource: Life cycle assessment of eco-friendly concrete in developing nations through energy transition - Yousaf Ali; Muhammad Salman Hassan; Antonella Petrillo (Journal of Cleaner Production, 2025)

Boosted proton conduction in LAO electrolyte through Li segregation for High-Performance ceramic fuel cells - Nabeela Akbar; Muhammad Yousaf; M.A.K. Yousaf Shah; Jahangeer Ahmed; Asma Noor; Quazi Arif Islam; Yan Wu; Saad M. Alshehri; Naveed Mushtaq; Bin Zhu; Sara Paydar (Fuel, 2025)

Machine learning-optimized trimetallic MOF integrated nanofibers for precise detection of p-Nitrophenol in agricultural soil - Ayesha Yousaf; Zhihua Zhao; Naeem Akhtar; Muhammad Aizaz; Maham Shahzadi (Chemical Engineering Journal, 2025)

Impacts of soiling on solar panel performance and state-of-the-art effective cleaning methods: A recent review - Nadia Shahzad; Naveed Hussain; Shayan Umar; Muhammad Farooq Azam; Tanzeela Yousaf; Adeel Waqas (Journal of Cleaner Production, 2025)

Ultrafine particles: Sources, toxicity, and deposition dynamics in the human respiratory tract —— experimental and computational approaches - Longfei Chen; Muhammad Yousaf; Jingsha Xu; Xiaoyan Ma (Journal of Environmental Management, 2025)

Effect of different colors and intensity of light emitting diode on the production performance, egg quality, hormonal profile and the economics of layers kept in environment control house - Ahmad Hamad Sheir; Fawwad Ahmad; Muhammad Yousaf; Rao Zahid Abbas (Tropical Animal Health and Production, 2025)

Effect of different likelihood measures on parameter conditioning and model uncertainty - Faisal Baig; Mehmet Cuneyd Demirel; Muhammad Yousaf Raza Taseer; Assaad Kassem; Mohsen Sherif (Stochastic Environmental Research and Risk Assessment, 2025)

Repurposing doxycycline for the inhibition of monkeypox virus DNA polymerase: a comprehensive computational study - Muhammad Abrar Yousaf; Maurice Michel; Abeedha Tu-Allah Khan; Misbah Noreen; Saddia Bano (In Silico Pharmacology, 2025)

Impact of forage levels and physical forms on feed sorting behavior, rumen morphometry, and selected blood parameters in fattening male goats - Muhammad Irfan Malik; Muhammad Afzal Rashid; Maria Teresa Capucchio; Muhammad Bilal; Muhammad Shahbaz Yousaf; Habib Ur Rehman; Amlan Kumar Patra (Small Ruminant Research, 2025)

Multiferroic Y Sn co-doped BiFeO3 2D nanoplates for enhanced photocatalytic degradation of cationic dyes: Synthesis, chemistry and mechanisms - Ahmad Umair; Mirza Mahmood Baig; Sheraz Yousaf; Muhammad Touqeer; Mehboob Hassan; Ali Ahmad; Joon Kim; Hyuntae Ju; Seung Goo Lee (Journal of Water Process Engineering, 2025)

Integration of physio-biological methods for remediation of dyes and toxic metals from textile wastewater - Muhammad Ayaz; Aqib Hassan Ali Khan; Kang Song; Asmat Ali; Sohail Yousaf; Abeer Kazmi; Abdur Rashid (Bioresource Technology Reports, 2025)

Moringa Biopriming with Zn Spray Improved Nutrients Rich Biofortified Chickpea Grains and Drought Tolerance at Reproductive Stages Under Arid Environment - Hamid Nawaz; Malik Muhammad Yousaf; Nazim Hussain; Tanveer Hussain; Malik Waqar Yousaf; Malik Ibrar Yousaf; Mona S. Alwahibi; Mohamed S. Elshikh; Baber Ali; Rashid Iqbal (Journal of Crop Health, 2025)

Influence of physical forms of non-forage diet on growth performance, feeding behavior, rumen and blood indices, and nutrient digestibility in fattening goats - Muhammad Bilal; Muhammad Irfan Malik; Muhammad Afzal Rashid; Muhammad Awais Khurshid; Muhammad Shahbaz Yousaf; Habib Ur Rehman (Small Ruminant Research, 2025)

High-Entropy Li-doped rock salt catalyst for low-Temperature ceramic fuel cells - Muhammad Khalid; M.A.K. Yousaf Shah; Nabeela Akbar; Naveed Mushtaq; Rizwan Raza; Jun Wang; Bin Zhu (Fuel, 2025)

The impact of the productive sectors on CO2 emissions in Pakistan - Muhammad Yousaf Raza; Boqiang Lin (Environmental Impact Assessment Review, 2025)

Unveiling concentrations of trace elements in the Lower Indus River: risks to aquatic life and human health - Muhammad Waseem Boota; Shan-e-hyder Soomro; Haoming Xia; Yaochen Qin; Muhammad Bilal Idrees; Ayesha Yousaf (Frontiers in Marine Science, 2024)
Concentration of trace elements (CTEs) is a significant environmental concern worldwide. This study assessed CTE levels in the Lower Indus River (LIR) by analyzing CTEs in water, sediments, tissues of fish ( Cirrhinus mrigala ), and macrophytes using electrothermal atomic absorption spectrometry (ETAAS) and flame atomic absorption spectrometry (FAAS). The study shows that CTE range—arsenic (As, 58.7–112.1 μg/L), lead (Pb, 59.9–95.6 μg/L), cadmium (Cd, 3.8–8.1 μg/L), nickel (Ni, 40.9–63.4 μg/L), and zinc (Zn, 590.7–847.6 μg/L)—and water parameters (temperature, pH, COD, BOD, turbidity, and alkalinity) exceeded WHO (World Health Organization) acceptable limits. The CTEs (mg/kg dried basis) were analyzed in fish tissues, and As, Cd, Cr, Cu, Hg, Ni, and Zn have the following accumulation order: liver > gill > muscle. In contrast, Ag and Pb were present in higher amounts in gills than in the liver (gill > liver > muscle). Prediction of bioavailability of CTEs, with the extraction of sediment load with EDTA, revealed that As, Cd, and Zn were among the most bioavailable elements in the LIR. Health risk assessment indicated that the presence of CTEs in the fish could pose potential adverse health effects on humans. The study emphasizes significant ecological and health concerns due to fish consumption in the affected region, noting high risks of non-carcinogenic effects. These insights are essential for policymakers and stakeholders in Sindh Province to manage and reduce trace element pollution.

The interactive antimicrobial activities of selected South African Terminalia spp. extracts in combination with conventional antibiotics against methicillin and β-lactam resistant pathogens - Muhammad Jawad Yousaf Zai; Matthew James Cheesman; Ian Edwin Cock (South African Journal of Botany, 2024)

A comprehensive review on ethno-pharmacological and phytochemical properties of selected species of genus Ophioglossum - Abdul Manan Yousaf; Sehrish Imran; Yamin Bibi; Muhammad Hasnain; Muhammad Imran Yousaf; Abdul Qayyum (South African Journal of Botany, 2024)

Chemical modification of Pinus walliichiana sawdust: Application in membrane system for efficient purification of groundwater containing Cd(II) and Ni(II) - Muhammad Imran Irfan; Mahnoor Sadiq; Lubna Zohra; Abu Bakar Siddique; Muhammad Yousaf; Madiha Rubab; Kishwar Urooj; Ambreen Aziz; Hira Ali; Mehreen Fatima; Hatem M.A. Amin; Hassan A. Alhazmi; et al. (Journal of Water Process Engineering, 2024)

Multilayered photo-bioanode for simultaneous conversion of CO2 and industrial refractory organics into bioelectricity in a microbial fuel cell system - Muhammad Ahmad; Maryam Yousaf; Aisha Batool; Hafiz Muhammad Adeel Sharif (Fuel, 2024)

The alleviating effects and mechanisms of Lactiplantibacillus plantarum MC14 on hyperuricemia in mice - Jie Xiong; Jia-Juan Wu; Dong-mei Liu; Muhammad Yousaf; Liu-Jun Liu; Suping Zeng; Qinqin Li; Jun Tang; Yaping Wu (Food Bioscience, 2024)

SNP Markers Associated with Some Root, Stolon, and Tuber Traits in Tetraploid Potatoes (Solanum tuberosum L.) Grown Under Diverse Growing Systems - Muhammad Farhan Yousaf; Ufuk Demirel; Muhammad Naeem; Eric Kuopuobe Naawe; Mehmet Emin Caliskan (Potato Research, 2024)
Numerous loci, environmental factors, and their interactions have an impact on the phenotypic diversity of several significant traits in plants. One approach put forth in recent years for genetic research and finding quantitative trait loci (QTLs) responsible for the specific trait is association mapping. The purpose of the current study was to pinpoint the genetic underpins of significant underground traits in potato. A panel of 192 diverse tetraploid potato genotypes from different countries were grown under different growing conditions (i.e., aeroponics and pot) to study root, stolon and tuber traits. Significant differences ( P ≤ 0.01) were found between the genotypes for all examined traits, and the heritability (H 2 ) of the traits ranged from 0.74 to 0.94. Genotyping was carried out using the SolCAP 25K array. 21,226 polymorphic SNPs were used for association mapping of underground traits. A GWASpoly R package was implemented for the marker-trait associations, and 78 genomic regions were found associated with the traits under investigation.. The history of potato breeding was reflected in LD patterns. The identified SNPs have their putative gene functions related to the root and stolon architecture and tuber growth (i.e., WRKY transcription factor, MAPK, the GTP cyclohydrolase 1 (i.e., GTPCHI ), Glutathionyl-hydroquinone reductase, and pyrophosphate—fructose 6-phosphate 1-phosphotransferase subunit alpha ( PFPase ). The results of the present study provides a framework that could be helpful for future potato breeding programs to increase tuber production and reduce the challenges of feeding the world's population in the years to come.

Pharmacological and immunomodulatory modes of action of medically important phytochemicals against arthritis: A molecular insight - Aqsa; Shaukat Ali; Muhammad Summer; Saima Yousaf; Laiba Nazakat; Shehzeen Noor (Molecular Biology Reports, 2024)

Vanillic Acid Enhances Mung Bean Resistance and Growth Against Macrophomina phaseolina as a Sustainable Antifungal Approach - Numan Ali; Amna Shoaib; Muhammad Rafiq; Barizah Malik; Muhammad Yousaf (Journal of Crop Health, 2024)

Improving the effect of air chambers on micro-pressure waves from tunnel portals: Moderate underdamping - Feng Liu; Haiyang Lei; Mengjie Wei; Huanwu Sun; Muhammad Yousaf Iqbal; Dawei Chen (Tunnelling and Underground Space Technology, 2024)

Spatial patterned solar evaporator for effective thermal management in enhanced solar-driven evaporation, and wastewater remediation - Naila Arshad; Muhammad Sohail Asghar; Muhammad Sultan Irshad; Najah Alwadie; Jinhua Li; M.A.K Yousaf Shah; Zhengbiao Ouyang; Hao Wang; Ho Xuan Nang; Van-Duong Dao; Xianbao Wang (Chemical Engineering Journal, 2024)

Assessment of uric acid-lowering activity, safety and stress tolerance of Lactiplantibacillus plantarum MC14 based on whole gene sequencing and phenotyping experiments - Jie Xiong; Lingxing Feng; Muhammad Yousaf; Suping Zeng; Jun Tang; Yaping Wu; Qinqin Li; Dong-mei Liu (Food Bioscience, 2024)

Mechanism of probiotics in the intervention of colorectal cancer: a review - Qinqin Li; Dongmei Liu; Minghua Liang; Yichao Zhu; Muhammad Yousaf; Yaping Wu (World Journal of Microbiology and Biotechnology, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

Evaluating the comprehensive flood impact assessment on the head reach of the Chiniot dam project - Shahzad Yousaf; Zohreh Rajabi; Muhammad Masood; M. Attiqurehman Tariq; Maria Talib; Ahmad Mujtaba (Total Environment Advances, 2024)

Recent advances in the detection and quantification of manufactured nanoparticles (MNPs) in complex environmental and biological matrices - Qumber Abbas; Muhammad Zia-ur-Rehman; Habib Ullah; Mehar Ahmed Mujtaba Munir; Muhammad Ubaid Ali; Amjad Ali; Krzysztof Pikon; Balal Yousaf (Journal of Cleaner Production, 2024)

Synergistic interactions and reaction mechanisms of biochar surface functionalities in antibiotics removal from industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Krzysztof Pikon (Environmental Pollution, 2024)

Inhibition of Monkeypox Virus DNA Polymerase Using Moringa oleifera Phytochemicals: Computational Studies of Drug-Likeness, Molecular Docking, Molecular Dynamics Simulation and Density Functional Theory - Muhammad Abrar Yousaf; Shefin Basheera; Sreekumar Sivanandan (Indian Journal of Microbiology, 2024)

Insights in to iron-based nanoparticles (hematite and magnetite) improving the maize growth (Zea mays L.) and iron nutrition with low environmental impacts - Nauman Yousaf; Muhammad Fahad Sardar; Muhammad Ishfaq; Baogang Yu; Yanting Zhong; Faisal Zaman; Fusuo Zhang; Chunqin Zou (Chemosphere, 2024)

An updated and gridded probabilistic seismic hazard assessment of Quetta city, Pakistan using multiple source models - Bilal Saif; Mohammad Tahir; Muhammad Ali Shah; Muhammad Naveed Mushtaq; Muhammad Yousaf Khan; Azmat Azad; Talat Iqbal (Journal of Asian Earth Sciences, 2024)

Retraction Note: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2024)

An innovative perovskite oxide enabling improved efficiency for low-temperature ceramic electrochemical cells - Yuzheng Lu; M. A. K. Yousaf Shah; Naveed Mushtaq; Muhammad Yousaf; Nabeela Akbar; Naila Arshad; Sultan Irshad (Fuel, 2024)

ConvEQ: Convolutional neural network for earthquake phase classification using short time frequency transform - Gul Rukh Khattak; Gul Muhammad Khan; Suhail Yousaf (Computers & Geosciences, 2024)

Insights into the biogeochemical transformation, environmental impacts and biochar-based soil decontamination of antimony - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Ayesha Imtiyaz Cheema; Samra Ijaz; Audil Rashid; Anila Sikandar; Krzysztof Pikoń (Environmental Research, 2024)

Methylotrophic bacteria from rice paddy soils: mineral-nitrogen-utilizing isolates richness in bulk soil and rhizosphere - Tabassum Yousaf; Fatima Saleem; Sahar Andleeb; Muhammad Ali; Muhammad Farhan Ul Haque (World Journal of Microbiology and Biotechnology, 2024)

Repurposing FDA approved drugs against monkeypox virus DNA dependent RNA polymerase: virtual screening, normal mode analysis and molecular dynamics simulation studies - Ahmad Abdul Salam Khan; Muhammad Abrar Yousaf; Jahanzaib Azhar; Muhammad Faisal Maqbool; Ruqia Bibi (VirusDisease, 2024)

Berberine ameliorates the progression of primary sclerosing cholangitis by activating farnesoid X receptor - Hassan Hameed; Nida Irshad; Muhammad Abrar Yousaf; Sidra Mumtaz; Imran Sohail (Cell Biochemistry and Biophysics, 2024)

Pakistan’s circular bio-economy: potential, opportunities and sustainable development - Yousaf Ali; Muhammad Sabir; Saad Afridi; Zahid Ullah (Environment, Development and Sustainability, 2024)

Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Supplementation of nano-biochar improved growth and physiological attributes in wheat seedlings exposed to salt stress through enhanced activity of hydrolysing and nitrogen metabolic enzymes and regulation of crucial metabolites - Waqas Yousaf; Anis Ali Shah; Muhammad Bilal Afzal; Zaib-un Nisa; Naila Ali; Muhammad Yasin Ashraf; Hosam O. Elansary; Aqeel Ahmad (South African Journal of Botany, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Dynamics of soil biota and nutrients at varied depths in a Tamarix ramosissima-dominated natural desert ecosystem: Implications for nutrient cycling and desertification management - Waqar Islam; Fanjiang Zeng; Afzal Ahmed Dar; Muhammad Sohail Yousaf (Journal of Environmental Management, 2024)

Long-term straw returning improved soil nitrogen sequestration by accelerating the accumulation of amino acid nitrogen - Lei Xu; Hong Chen; Yan Zhou; Jianwei Zhang; Muhammad Yousaf Nadeem; Congrong Miao; Jiahui You; Weiwei Li; Yu Jiang; Yanfeng Ding; Ganghua Li (Agriculture, Ecosystems & Environment, 2024)

Heart rate as an indicator of stress during the critical swimming speed test of farmed Atlantic salmon ( Salmo salar L.) - Muhammad Naveed Yousaf; Øyvind Røn; Frederike Keitel‐Gröner; Charles McGurk; Alex Obach (Journal of Fish Biology, 2024)
A swim tunnel is to fish as a treadmill is to humans, and is a device used for indirect measuring of the metabolic rate. This study aims to explore the fish stress (if any) during the critical swimming test routines (fish handling, confinement, and swimming) using heart rate ( f H , heartbeat per minute) bio‐loggers in farmed Atlantic salmon ( Salmo salar L.). In addition, the recovery dynamics of exercised fish using f H were explored for 48 h post swim tests. Continuous f H data were acquired following the surgical implantation and throughout the trials, such as during fish handling, swim tests (critical swimming speed, U crit ), and 48 h post swim tests. After 3 weeks of surgical recovery, f H stabilized at 46.20 ± 1.26 beats min −1 , equalizing a ~38% reduction in f H recorded post‐surgical tachycardia (74.13 ± 1.44 beats min −1 ). Interestingly, f H was elevated by ~200% compared to baseline levels not only due to the U crit (92.04 ± 0.23 beats min −1 ) but also due to fish handling and confinement in the swim tunnel, which was 66% above the baseline levels (77.48 ± 0.34 beats min −1 ), suggesting fish stress. Moreover, significantly higher plasma cortisol levels (199.56 ± 77.17 ng mL −1 ) corresponding to a ~300% increase compared to baseline levels (47.92 ± 27.70 ng mL −1 ) were identified after U crit , predicting post‐swim test stress (physiological exhaustion). These findings reinforce the importance of fish acclimation in the swim tunnel prior to the swimming tests. However, f H dropped over the course of the 48‐h post‐swim test, but remained comparatively higher than the basal levels, suggesting fish should be given at least 48 h to recover from handling stress for better fish welfare. This study further explored the influence of fish tagging on U crit , which resulted in reduced swimming capabilities of tagged fish (1.95 ± 0.37 body lengths s −1 ) compared to untagged fish (2.54 ± 0.42 body length s −1 ), although this was not significant ( p = 0.06), and therefore future tagging studies are warranted.

Correction to: Differential responses of Brassica napus cultivars to dual effects of magnesium oxide nanoparticles - Sharafat Ali; Zaid Ulhassan; Skhawat Ali; Zohaib Kaleem; Muhammad Arslan Yousaf; Mohamed S. Sheteiwy; Shafaqat Ali; Muhammad Waseem; Sanaullah Jalil; Jian Wang; Weijun Zhou (Environmental Science and Pollution Research, 2024)

FinTech-powered integration: Navigating the static and dynamic connectedness between GCC equity markets and renewable energy cryptocurrencies - Shoaib Ali; Muhammad Naveed; Manel Youssef; Imran Yousaf (Resources Policy, 2024)

Differential responses of Brassica napus cultivars to dual effects of magnesium oxide nanoparticles - Sharafat Ali; Zaid Ulhassan; Skhawat Ali; Zohaib Kaleem; Muhammad Arslan Yousaf; Mohamed S. Sheteiwy; Shafaqat Ali; Muhammad Waseem; Sanaullah Jalil; Jian Wang; Weijun Zhou (Environmental Science and Pollution Research, 2024)

Sustainable energy changeover in Pakistan: prospects, progress, and policies - Muhammad Yousaf Raza; Marco Cucculelli (Environmental Science and Pollution Research, 2024)

Copolymerization of ethylene and isoprene via silicon bridge metallocene [rac-Me2Si(2-Me-4-Ph-Ind)2ZrCl2] catalyst: A new way to control the composition and microstructure of copolymers - Amjad Ali; Ahmad Naveed; Anna Maroń; Muhammad Adnan Younis; Jamile Mohammadi Moradian; Balal Yousaf; Tariq Aziz; Rai Nauman Ali; Naushad Ahmad; Suliman Yousef Alomar; Fan Zheqiang; Li Guo (Chemosphere, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Oxygen-regulated spontaneous solid electrolyte interphase enabling ultra-stable solid-state Na metal batteries - Keshuang Cao; Yufan Xia; Haosheng Li; Huiqin Huang; Sikandar Iqbal; Muhammad Yousaf; Ben Bin Xu; Wenping Sun; Mi Yan; Hongge Pan; Yinzhu Jiang (Science Bulletin, 2024)

Therapeutic Physical Properties, Photocatalytic, and Anti-bacterial Activities of Hydrothermally Fabricated Cu-doped ZnO NPs - Muhammad Zahid Ishaque; Yasir Zaman; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Hira Zaman; Sarmad Ali; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Cassia Angustifolia Primed ASCs Accelerate Burn Wound Healing by Modulation of Inflammatory Response - Saba Tasneem; Hafiz Ghufran; Maryam Azam; Amna Arif; Musab Bin Umair; Muhammad Amin Yousaf; Khurrum Shahzad; Azra Mehmood; Kausar Malik; Sheikh Riazuddin (Tissue Engineering and Regenerative Medicine, 2024)

Characterization of water-deficit tolerance in Upland cotton (Gossypium hirsutum L.) assessing morphological, biochemical, molecular and yield attributes - Muhammad Saeed; Muhammad Naeem; Alia Javed; Shagufta Perveen; Iqra Sajjad; Muhammad Zaid Yousaf; M. Shahid Munir Chohan; Muhammad Riaz; Sana Ullah; Xianliang Song (Acta Physiologiae Plantarum, 2024)

Influence of biochar produced from negative pressure-induced carbonization on transformation of potentially toxic metal(loid)s concerning plant physiological characteristics in industrially contaminated soil - Ayesha Imtiyaz Cheema; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muyuan Lu; Samina Irshad; Krzysztof Pikon; Mehr Ahmed Mujtaba Munir; Muhammad Saqib Rashid (Journal of Environmental Management, 2023)

Synergistic effect of extracellular adenosine triphosphate and quercetin on post-thaw quality and fertilization potential of Lohi ram sperm - Muhammad Tayyab Khan; Muhammad Irfan-ur-Rehman Khan; Ejaz Ahmad; Muhammad Rizwan Yousaf; Muhammad Oneeb (Cryobiology, 2023)

State-of-the-art analysis of the fuel desulphurization processes: Perspective of CO2 utilization in coal biodesulphurization - Muhammad Ahmad; Maryam Yousaf; Jing-Cheng Han; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Linlin Wang; Zhaozhao Tang; Yang Zhou; Yuefei Huang (Chemical Engineering Journal, 2023)

Development of a new hybrid ensemble method for accurate characterization of future drought using multiple global climate models - Mahrukh Yousaf; Zulfiqar Ali; Muhammad Mohsin; Maryam Ilyas; Muhammad Shakeel (Stochastic Environmental Research and Risk Assessment, 2023)

Controlled-release potassium blended fertilizer mitigates greenhouse gas emissions in paddy fields - Sajjad Ahmad; Shen Gao; Quanxin Li; Muhammad Yousaf Nadeem; Weike Tao; Fei Yang; Yanfeng Ding; Zhenghui Liu; Ganghua Li (Nutrient Cycling in Agroecosystems, 2023)

Autoregressive conditional duration modeling and forecasting the earthquakes temporal data of the different regions of Pakistan - Muhammad Yousaf Khan; Stefan Mittnik; Mohammad Tahir; Muhammad Ali Shah; Talat Iqbal (Acta Geophysica, 2023)

Inquiring the impact of rural–urban migration, construction sector, and agriculture irrigated land on environmental degradation: insights from urbanized Asian countries - Feng Guoru; Muhammad Haris Hanif; Usman Saleem Yousaf (Environmental Science and Pollution Research, 2023)

Multiple phases of yttrium-doped molybdenum trioxide nanorods as efficient dye degrader and bactericidal agents with molecular docking analysis - Muhammad Ikram; Tahira Shujah; Anum Shahzadi; Ali Haider; Aqsa Rafique; Anwar Ul-Hamid; Walid Nabgan; Syed Karrar Haider; Thamraa Alshahrani; Mohammed M. Algaradah; S. Amber Yousaf; Junaid Haider (Chemosphere, 2023)

Circular economy and its implementation in cement industry: A case point in Pakistan - Azfar Uddin; Yousaf Ali; Muhammad Sabir; Antonella Petrillo; Fabio De Felice (Science of The Total Environment, 2023)

3D cellular lattice like-Ti3C2 MXene based aerogels embedded with metal selenides particles for energy storage and water splitting applications - Khadija Chaudhary; Beriham Basha; Sonia Zulfiqar; Sheraz Yousaf; Eric W. Cochran; M.S. Al-Buriahi; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2023)

Exploring perovskite oxide for advancing salt-resistant photothermal membranes and reliable thermoelectric generators - Naila Arshad; Muhammad Sultan Irshad; Muneerah Alomar; Jinming Guo; M. Sohail Asghar; Naveed Mushtaq; M.A.K. Yousaf; Uzma Ghazanfar; Matiullah Shah; Xianbao Wang; Yabin Hao; Lien Thi Do; et al. (Chemical Engineering Journal, 2023)

Asymmetric efficiency in petroleum markets before and during COVID-19 - Muhammad Abubakr Naeem; Saqib Farid; Imran Yousaf; Sang Hoon Kang (Resources Policy, 2023)

Tailoring triple charge (O2−/H+/e−) conducting nature of Fe-based lanthanum doped samarium oxides for ceramic fuel cells (CFCs) - Muhammad Yousaf; Yuzheng Lu; Majid Niaz Akhtar; Ali Sarosh Khawaja; Khalid Mujasam Batoo; Sajjad Hussain; Asma Noor; Muhammad Akbar; Hu Enyi; M.A.K Yousaf Shah; Naveed Mushtaq; Bin Zhu (Fuel, 2023)

Analysis of energy-related CO2 emissions in Pakistan: carbon source and carbon damage decomposition analysis - Muhammad Yousaf Raza; LI Dongsheng (Environmental Science and Pollution Research, 2023)

Effect of NDF levels of complete pelleted diet and dietary transition period on rumen pH, growth performance, digestibility, and blood indices in fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

Corrigendum to “Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns” [Cryobiology 110 (2023) 69–78] - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Ginsenosides in cancer: Targeting cell cycle arrest and apoptosis - Muhammad Ajmal Shah; Syed Muhammad Abuzar; Kainat Ilyas; Irtaza Qadees; Momna Bilal; Rimsha Yousaf; Roaa Mohammed Tahir Kassim; Azhar Rasul; Uzma Saleem; Maria Silvana Alves; Haroon Khan; Renald Blundell; et al. (Chemico-Biological Interactions, 2023)

Cloning and functional analysis of the DXR gene and promoter region in Osmanthus fragrans var. semperflorens - Zihan Wang; Taimoor Hassan Farooq; Hanjie He; Aitzaz A.A. Shahani; Rashida Hameed; Amna Fayyaz; Muhammad Sohail Yousaf; Jun Wang; Lili Chen (Functional & Integrative Genomics, 2023)

Recent advances in chromosome capture techniques unraveling 3D genome architecture in germ cells, health, and disease - Nuruliarizki Shinta Pandupuspitasari; Faheem Ahmed Khan; Chunjie Huang; Azhar Ali; Muhammad Rizwan Yousaf; Farwa Shakeel; Ezi Masdia Putri; Windu Negara; Anis Muktiani; Bambang Waluyo Hadi Eko Prasetiyono; Limbang Kustiawan; Dimar Sari Wahyuni (Functional & Integrative Genomics, 2023)

Physical properties of multifunctional TM-doped ZnO nanorods and their photocatalytic and anti-bacterial activities - Yasir Zaman; Muhammad Zahid Ishaque; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Muhammad Imran Arshad; Muhammad Sajid; Nisar Ali; Ghulam Nabi (Environmental Science and Pollution Research, 2023)

Strategic analysis on development of simultaneous adsorption and catalytic biodegradation over advanced bio-carriers for zero-liquid discharge of industrial wastewater - Jing-Cheng Han; Muhammad Ahmad; Maryam Yousaf; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Yang Zhou; Bo Yang; Yuefei Huang (Chemosphere, 2023)

Feed intake, feeding behavior, growth performance, nutrient digestibility, and carcass characteristics of goats fed pelleted total mixed rations with varying Rhodes hay levels - Muhammad Irfan Malik; Xuezhao Sun; Muhammad Afzal Rashid; Muhammad Amer Sohail; Muhammad Shahbaz Yousaf; Habib Ur Rehman; Imran Mohsin; Jianping Li (Small Ruminant Research, 2023)

Development of biocatalytic microbial ecosystem (FPUS@RODMs@In-PAOREs) for rapid and sustainable degradation of various refractory organics - Muhammad Ahmad; Maryam Yousaf; Jing-Cheng Han; Yuefei Huang; Yang Zhou; Zhaozhao Tang (Journal of Hazardous Materials, 2023)

Spectroscopic fingerprinting, pollution characterization, and health risk assessment of potentially toxic metals from urban particulate matter - Abdul Rehman; Guijian Liu; Balal Yousaf; Samra Ijaz; Samina Irshad; Ayesha Imtiyaz Cheema; Muhammad Umair Riaz; Aniqa Ashraf (Environmental Science and Pollution Research, 2023)

Sustainable utilization of apple pomace and its emerging potential for development of functional foods - Muhammad Asif; Tahreem Javaid; Zafar Ullah Razzaq; Muhmmad Kashif Iqbal Khan; Abid Aslam Maan; Saria Yousaf; Ayesha Usman; Sidra Shahid (Environmental Science and Pollution Research, 2023)

Correction to: Two-dimensional hydrodynamic modeling for prediction of bank erosion and bed incision in the Indus River - Muhammad Waseem Boota; Chaode Yan; Shan-e-hyder Soomro; Muhammad Awais Zafar; Ziwei Li; Jikun Xu; Ayesha Yousaf (Acta Geophysica, 2023)

The role of carbon pricing in the relationship between air freight and environmental resource depletion: a case study of Saudi Arabia - Muhammad Khalid Anser; Zahid Yousaf; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Clean Technologies and Environmental Policy, 2023)

Two-dimensional hydrodynamic modeling for prediction of bank erosion and bed incision in the Indus River - Muhammad Waseem Boota; Chaode Yan; Shan-e-hyder Soomro; Muhammad Awais Zafar; Ziwei Li; Jikun Xu; Ayesha Yousaf (Acta Geophysica, 2023)

Impregnation of biochar with montmorillonite and its activation for the removal of azithromycin from aqueous media - Muhammad Arif; Guijian Liu; Muhammad Zia ur Rehman; Md Manik Mian; Aniqa Ashraf; Balal Yousaf; Muhammad Saqib Rashid; Rafay Ahmed; Muhammad Imran; Mehr Ahmed Mujtaba Munir (Environmental Science and Pollution Research, 2023)

Dynamic spillovers and portfolio risk management between defi and metals: Empirical evidence from the Covid-19 - Shoaib Ali; Muhammad Shahzad Ijaz; Imran Yousaf (Resources Policy, 2023)

Valorization of palm tree (Phoenix dactylifera L.) leaves from harsh weather climate by silage using endogenous lactic acid bacteria, and application of MALDI-TOF MS for study of populations dynamics - Muhammad Zaid Jawaid; Mohammad Yousaf Ashfaq; Mohammad Al-Ghouti; Nabil Zouari (Bioresource Technology Reports, 2023)

Epidemiological survey of bovine gammaherpesvirus 4 (BoHV-4) infection in cattle and buffalo from Pakistan - Anees Khalid; Aayesha Riaz; Arfan Yousaf; Irtaza Hassan Khan; Saif Ur-Rehman; Muhammad Moaeen-ud-Din; Song Li; Congli Tang; Muhammad Ali Shah; Murtaz-ul-Hasan (Veterinary Research Communications, 2023)

Replacing ground Rhodes grass hay with soyhulls in the pelleted diet: effects on ingestive behavior, nutrient digestibility, blood metabolites, growth performance, and economic viability of intensive fattening Lohi lambs - Muhammad Khan; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Imran Mohsin; Habib Ur Rehman (Tropical Animal Health and Production, 2023)

Risk assessment of circular economy practices in construction industry of Pakistan - Muhammad Salman Hassan; Yousaf Ali; Antonella Petrillo; Fabio De Felice (Science of The Total Environment, 2023)

Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Effect of straw particle size in high grain complete pelleted diet on growth performance, rumen pH, feeding behavior, nutrient digestibility, blood and carcass indices of fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

Future outlook and influencing factors analysis of natural gas consumption in Bangladesh: An economic and policy perspectives - Muhammad Yousaf Raza; Boqiang Lin (Energy Policy, 2023)

Formulation of heterometallic ZIF-8@Cu/Ni/ZnO@CNTs heterostructure photocatalyst for Ultra-Deep desulphurization of coal and fuels - Muhammad Ahmad; Maryam Yousaf; Weiwei Cai; Zhi-Ping Zhao (Chemical Engineering Journal, 2023)

Role of biochar-based free radicals in immobilization and speciation of metals in the contaminated soil-plant environment - Muhammad Saqib Rashid; Guijian Liu; Balal Yousaf; Yasir Hamid; Abdul Rehman; Muhammad Arif; Rafay Ahmed; Yu Song; Aniqa Ashraf (Journal of Environmental Management, 2023)

An overview of genome-wide association mapping studies in Poaceae species (model crops: wheat and rice) - Muhammad Abu Bakar Zia; Muhammad Farhan Yousaf; Arslan Asim; Muhammad Naeem (Molecular Biology Reports, 2022)

Genetic diversity and population structure assessed through simple sequence repeat markers in Saccharum spp. hybrids from Pakistan and Sri Lanka - Sundas Shahzad; Muhammad Saeed; Shagufta Perveen; Muhammad Azeem; Iqra Sajjad; Shazia Saeed; Muhammad Naeem; Alia Javed; Iqra Sultan; Ukasha Faria; Sana Maryam; Muhammad Zaid Yousaf (Genetic Resources and Crop Evolution, 2022)

Does location of the households’ matters? Identifying the households’ willingness to pay and preference heterogeneity in advancement of vulnerable ecosystem services: An approach of choice experiment - Muhammad Abu Sufyan Ali; Zhihe Zhang; Sufyan Ullah Khan; Arshad Ahmad Khan; Mohammad Musa; Preethu Rahman; Yousaf Hayat (Environmental Science and Pollution Research, 2022)

Bentonite binding with mercury(II) ion through promotion of reactive oxygen species derived from manure-based dissolved organic matter - Saeed Rehman; Sayyaf Yousaf; Quanyun Ye; Liu Chenhui; Muhammad Bilal; Ahson Jabbar Shaikh; Muhammad Saqib Khan; Sohail Anjum Shahzad; Pingxiao Wu (Environmental Science and Pollution Research, 2022)

A comparative analysis of renewable and non-renewable energy generation to relegate CO2 emissions and general costs in household systems - Mudassar Hussain; Manzoor Sultan; Faiza Uzma; Cheng Longsheng; Muhammad Yousaf Malik; Abdul Rahman Butt; Aqsa Sajjad; Ijaz Younis; Muhammad Imran (Environmental Science and Pollution Research, 2022)

Photosynthetic Efficiency and Antioxidant Defense Potential are Key Players in Inducing Drought Tolerance in Transgenic Tobacco Plants Over-Expressing AVP1 - Hamid Manzoor; Muhammad Shahzad Anjam; Fozia Saeed; Sumaira Rasul; Saira Yousaf; Ayesha Kirn; Muhammad Kamran Qureshi; Zafar Ullah Zafar; Muhammad Ashraf; Habib-ur-Rehman Athar (Journal of Plant Growth Regulation, 2022)

Energy-growth hypothesis: testing non-linearity by considering production function approach for Spanish economy - Muhammad Shahid Hassan; Haider Mahmood; Saba Yousaf (Environmental Science and Pollution Research, 2022)

Evaluation of histological post‐mortem changes in farmed Atlantic salmon ( Salmo salar L.) at different time intervals and storage temperatures - Lisa Furnesvik; Toni Erkinharju; Miroslava Hansen; Muhammad Naveed Yousaf; Tore Seternes (Journal of Fish Diseases, 2022)
The aim of this study was to evaluate histologic post‐mortem autolytic changes in farmed Atlantic salmon. The fish were either stored at room temperature (RT, 21°C), refrigerated (4°C) or frozen (−20°C), while fish necropsy was performed at 0, 1, 4, 24 and 48 h post‐storage (hps). In addition, gills were sampled at 0, 5, 10, 15, 30 and 45 min post‐storage (mps) at room temperature (RT). The haematoxylin and eosin‐stained tissue slides were evaluated and scored by using a semi‐quantitative scoring system. Our findings demonstrated gills and pyloric caeca/pancreas as the most severely autolysed organs while heart and skeletal musculature were least affected. Generally, moderate to severe autolysis appeared first at 4 hps, while severe changes were seen at 24 hps. Gills demonstrated autolytic changes as early as 10 mps and pyloric caeca/pancreas at 1 hps. Freezing did not prevent the autolysis and even contributed to freezing artefacts, which may lead to misdiagnosis. Keeping organs refrigerated slowed the autolytic progress within the first 4 hps marginally. This study recommends gills and pyloric caeca/pancreas should be sampled as early as possible, at least within 10 min post‐necropsy.

Performance analysis of kinetic models in predicting asphaltene precipitation rate under different conditions of temperature and percentage of precipitant molecular weight - Syed Imran Ali; Shaine Mohammadali Lalji; Zahoor Awan; Saud Hashmi; Muhammad Noman; Nimra Yousaf (Arabian Journal of Geosciences, 2022)

Nexus between fossil fuel consumption and infant mortality rate: a non-linear analysis - Maqbool Hussain Sial; Noman Arshed; Muhammad Asif Amjad; Yousaf Ali Khan (Environmental Science and Pollution Research, 2022)

Phyto-mediated photocatalysis: a critical review of in-depth base to reactive radical generation for erythromycin degradation - Aniqa Ashraf; Guijian Liu; Balal Yousaf; Muhammad Arif; Rafay Ahmed; Audil Rashid; Luqman Riaz; Muhammad Saqib Rashid (Environmental Science and Pollution Research, 2022)

Multi-step short-term $$PM_{2.5}$$ forecasting for enactment of proactive environmental regulation strategies - Saba Gul; Gul Muhammad Khan; Sohail Yousaf (Environmental Monitoring and Assessment, 2022)

Pollution characteristics, mechanism of toxicity and health effects of the ultrafine particles in the indoor environment: Current status and future perspectives - Muhammad Ubaid Ali; Siyi Lin; Balal Yousaf; Qumber Abbas; Mehr Ahmed Mujtaba Munir; Audil Rashid; Chunmiao Zheng; Xingxing Kuang; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2022)

Soil conditioners improve rhizodegradation of aged petroleum hydrocarbons and enhance the growth of Lolium multiflorum - Fida Hussain; Aqib Hassan Ali Khan; Imran Hussain; Asifa Farooqi; Yousaf Shad Muhammad; Mazhar Iqbal; Muhammad Arslan; Sohail Yousaf (Environmental Science and Pollution Research, 2022)

Towards a sustainable development: econometric analysis of energy use, economic factors, and CO2 emission in Pakistan during 1975–2018 - Muhammad Yousaf Raza (Environmental Monitoring and Assessment, 2022)

Phenomena, factors of wax deposition and its management strategies - Syed Imran Ali; Shaine Mohammadali Lalji; Javed Haneef; Muhammad Arqam Khan; Mohsin Yousufi; Nimra Yousaf; Abdus Saboor (Arabian Journal of Geosciences, 2022)

Comparative study of flash flood in ungauged watershed with special emphasizing on rough set theory for handling the missing hydrological values - Muhammad Waseem Boota; Chaode Yan; Tanveer Abbas; Ziwei Li; Ming Dou; Ayesha Yousaf (Natural Hazards, 2021)

Comparative analysis of chicken cecal microbial diversity and taxonomic composition in response to dietary variation using 16S rRNA amplicon sequencing - Zubia Rashid; Muhammad Zubair Yousaf; Syed Muddassar Hussain Gilani; Sitwat Zehra; Ashaq Ali; Abid Azhar; Saddia Galani (Molecular Biology Reports, 2021)

Socio-economic and corporate factors and COVID-19 pandemic: a wake-up call - Muhammad Khalid Anser; Sheikh Usman Yousaf; Shabir Hyder; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2021)

The role of food crop production, agriculture value added, electricity consumption, forest covered area, and forest production on CO2 emissions: insights from a developing economy - Muhammad Yousaf Raza; Ali Nawaz Khan; Naseer Abbas Khan; Allauddin Kakar (Environmental Monitoring and Assessment, 2021)

Geochemical fractionation and spectroscopic fingerprinting for evaluation of the environmental transformation of potentially toxic metal(oid)s in surface–subsurface soils - Samina Irshad; Guijian Liu; Balal Yousaf; Muhammad Ubaid Ali; Rafay Ahmed; Abdul Rehman; Muhammad Saqib Rashid; Yusra Mahfooz (Environmental Geochemistry and Health, 2021)

Correction to: Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Investigating household sector’s non-renewables, biomass energy consumption and carbon emissions for Pakistan - Hazrat Yousaf; Azka Amin; Amdadullah Baloch; Muhammad Akbar (Environmental Science and Pollution Research, 2021)

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Innovative initiative for effective operation and monitoring using HEC‐RAS modelling of Hakra Branch Canal System, Pakistan * - Muhammad Kamran; Wasif Yousaf; R.L.H.L. Rajapakse; Wakas Kareem Awan; Muhammad Riaz; Nayyar Minhaj Asif; Muhammad Umar; Usman Tehsin Shah (Irrigation and Drainage, 2021)
The Punjab Irrigation System is one of the world's largest contiguous systems, with its entire network extending over nearly 31,000 km in length. The system faces numerous constraints that limit the canal operations and their respective design discharges. Shortage of irrigation water is a contest that normally occurs at canal tail‐end users. The hydraulic performance of open canal networks is not easy to assess; therefore, it is impossible to feed the lateral offtakes with their design shares without changing designed or existing gate openings. To overcome these problems, a Hydrologic Engineering Center's River Analysis System (HEC‐RAS) model has been developed to simulate the flow situation in the canal system. For this study, the Hakra Branch Canal System with a command area of 1.4 million hectares was selected. To recognize model performance, water levels at the head of the canal and tail discharge have been compared with field data. The simulated results show the best‐fit match with field head water levels with coefficients of determination ( R 2 ) of 0.765 and 0.877 and tail discharges of the canal with R 2 = 0.707 and 0.945, for calibration and validation periods, respectively. The hydraulic simulation model is a useful tool for effective canal operation to determine the losses and find out the expected discharge for the tail‐end users. It has been observed that the proportion of excess actual delivery of water to lateral offtakes results in inadequate water supply for the tail‐end users. It is recommended that during the observation of the seasonally discharge table, the irrigation engineer should adjust a factor either in the HEC‐RAS model or in the observed data. It is also recommended to develop an unsteady model for considering sediment transport.

Emission sources and full spectrum of health impacts of black carbon associated polycyclic aromatic hydrocarbons (PAHs) in urban environment: A review - Muhammad Ubaid Ali; Lin Siyi; Balal Yousaf; Qumber Abbas; Rashida Hameed; Chunmiao Zheng; Xingxing Kuang; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2021)

Optimization, in vitro release and toxicity evaluation of novel pH sensitive itaconic acid-g-poly(acrylamide)/sterculia gum semi-interpenetrating networks - Fauzia Rehman; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Akhtar Rasul; Huma Mahmood; Abid Mehmood Yousaf; Yasser Shahzad; Muhammad Mudassar; Noor Ul Amin Mohsin (DARU Journal of Pharmaceutical Sciences, 2021)

Rising Metals Concentration in the Environment: A Response to Effluents of Leather Industries in Sialkot - Noreen Khalid; Zarrin Fatima Rizvi; Nousheen Yousaf; Shujaul Mulk Khan; Ali Noman; Muhammad Aqeel; Komal Latif; Asmara Rafique (Bulletin of Environmental Contamination and Toxicology, 2021)

Chemiluminescent-microparticle-immunoassay-based detection and prevalence of human immunodeficiency virus infection in Islamabad, Pakistan - Misbahud Din; Faheem Anwar; Muhammad Ali; Muhammad Yousaf; Bilal Ahmad; Abdullah (Archives of Virology, 2021)

Earthquake stochastic modeling and estimating the probabilities of earthquake occurrences in Hindu Kush region - Muhammad Yousaf Khan; Muhammad Ali Shah; Fehmeeda Khanam (Arabian Journal of Geosciences, 2021)

Allelopathic hormesis and potent allelochemicals from multipurpose tree Moringa oleifera leaf extract - Shagufta Perveen; Muhammad Naeem Mushtaq; Muhammad Yousaf; Nighat Sarwar (Plant Biosystems, 2021)

Environmental transformation and nano-toxicity of engineered nano-particles (ENPs) in aquatic and terrestrial organisms - Qumber Abbas; Balal Yousaf; Habib Ullah; Muhammad Ubaid Ali; Yong Sik Ok; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2020)

Probabilistic Modeling of Earthquake Interevent Times in Different Regions of Pakistan - Muhammad Yousaf Khan; Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah (Pure and Applied Geophysics, 2020)

Correction to: Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Methanolic extract of Ephedra ciliata promotes wound healing and arrests inflammatory cascade in vivo through downregulation of TNF-α - Hafiza Sidra Yaseen; Muhammad Asif; Malik Saadullah; Mahrukh; Sajid Asghar; Muhammad Usman Shams; Rizwan Rashid Bazmi; Mohammad Saleem; Hafiz Muhammad Yousaf; Maria Yaseen (Inflammopharmacology, 2020)

Economic impact assessment of natural disaster with multi-criteria decision making for interdependent infrastructures - Muhammad Abdullah Khalid; Yousaf Ali (Environment, Development and Sustainability, 2020)

Structural changes in carbon dioxide (CO2) emissions in the United Kingdom (UK): an emission multiplier product matrix (EMPM) approach - Yousaf Ali; Rosita Pretaroli; Muhammad Sabir; Claudio Socci; Francesca Severini (Mitigation and Adaptation Strategies for Global Change, 2020)

The potential and efficacy of Allium sativum leaf lectin (ASAL) against sap-sucking insect pests of transgenic maize - Muhammad Umar Bhatti; Saman Riaz; Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Iqra Yousaf; Muhammad Tariq; Shahid Murtaza; Idrees Ahmad Nasir; Bushra Tabassum (Biologia, 2020)

Enhanced uptake of Cd, Cr, and Cu in Catharanthus roseus (L.) G.Don by Bacillus cereus: application of moss and compost to reduce metal availability - Muhammad Umair Mushtaq; Ameena Iqbal; Ismat Nawaz; Cyrus Raza Mirza; Sohail Yousaf; Ghazanfar Farooq; Muhammad Arif Ali; Aqib Hassan Ali Khan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Analysis of coal-related energy consumption in Pakistan: an alternative energy resource to fuel economic development - Muhammad Yousaf Raza; Muhammad Tauqir Sultan Shah (Environment, Development and Sustainability, 2020)

Social and administrative issues related to the COVID-19 pandemic in Pakistan: better late than never - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Xuan Hinh Vo; Khalid Zaman (Environmental Science and Pollution Research, 2020)

The impacts of COVID-19 measures on global environment and fertility rate: double coincidence - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Xuan Hinh Voo; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Air Quality, Atmosphere & Health, 2020)

Evaluation of Acer rubrum Tree Bark as a Bioindicator of Atmospheric Heavy Metal Pollution in Toronto, Canada - Muhammad Yousaf; Khakhathi L. Mandiwana; Khurram S. Baig; Julia Lu (Water, Air, & Soil Pollution, 2020)

Advances in exogenous RNA delivery techniques for RNAi-mediated pest control - Olawale Samuel Adeyinka; Saman Riaz; Nida Toufiq; Iqra Yousaf; Muhammad Umar Bhatti; Anicet Batcho; Amos Afolarin Olajide; Idrees Ahmad Nasir; Bushra Tabassum (Molecular Biology Reports, 2020)

Development of green methodologies for Heck, Chan–Lam, Stille and Suzuki cross-coupling reactions - Muhammad Yousaf; Ameer Fawad Zahoor; Rabia Akhtar; Matloob Ahmad; Shazia Naheed (Molecular Diversity, 2020)

Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Role of public-private partnerships investment in energy and technological innovations in driving climate change: evidence from Brazil - Mahmood Ahmad; Muhammad Yousaf Raza (Environmental Science and Pollution Research, 2020)

Evolutionarily conserved and testis-specific gene, 4930524B15Rik, is not essential for mouse spermatogenesis and fertility - Ranjha Khan; Jingwei Ye; Ayesha Yousaf; Wasim Shah; Ayesha Aftab; Basit Shah; Qamar Zaman; Muhammad Zubair; Qinghua Shi; Xiaohua Jiang (Molecular Biology Reports, 2020)

Does financial development and foreign direct investment improve environmental quality? Evidence from belt and road countries - Mahmood Ahmad; Ping Jiang; Abdul Majeed; Muhammad Yousaf Raza (Environmental Science and Pollution Research, 2020)

Influence of Pseudomonas japonica and organic amendments on the growth and metal tolerance of Celosia argentea L. - Ameena Iqbal; Muhammad Umair Mushtaq; Aqib Hassan Ali Khan; Ismat Nawaz; Sohail Yousaf; Zeshan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

The impact of tourism and natural resources on the ecological footprint: a case study of ASEAN countries - Nattapan Kongbuamai; Quocviet Bui; Hafiz Muhammad Abaid Ullah Yousaf; Yun Liu (Environmental Science and Pollution Research, 2020)

Resistance to Chilo infuscatellus (Lepidoptera: Pyraloidea) in transgenic lines of sugarcane expressing Bacillus thuringiensis derived Vip3A protein - Saman Riaz; Idrees Ahmad Nasir; Muhammad Umar Bhatti; Olawale Samuel Adeyinka; Nida Toufiq; Iqra Yousaf; Bushra Tabassum (Molecular Biology Reports, 2020)

Environmental risk assessment of diclofenac residues in surface waters and wastewater: a hidden global threat to aquatic ecosystem - Hafsa Hanif; Amir Waseem; Sundas Kali; Naveeda Akhtar Qureshi; Muhammad Majid; Mazhar Iqbal; Tofeeq Ur-Rehman; Muhammad Tahir; Sohail Yousaf; Muhammad Mazhar Iqbal; Imtiaz Ahmad Khan; Mazhar Iqbal Zafar (Environmental Monitoring and Assessment, 2020)

Natural and semisynthetic polymers blended orodispersible films of citalopram - Yasser Shahzad; Maimoona Maqbool; Talib Hussain; Abid Mehmood Yousaf; Ikram Ullah Khan; Tariq Mahmood; Muhammad Jamshaid (Natural Product Research, 2020)

International tourism, social distribution, and environmental Kuznets curve: evidence from a panel of G-7 countries - Muhammad Khalid Anser; Zahid Yousaf; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Estimating the pollution characteristics and health risks of potentially toxic metal(loid)s in urban-industrial soils in the Indus basin, Pakistan - Samina Irshad; Guijian Liu; Balal Yousaf; Habib Ullah; Muhammad Ubaid Ali; Jörg Rinklebe (Environmental Monitoring and Assessment, 2019)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Modulation in growth, gas exchange, and antioxidant activities of salt-stressed rice (Oryza sativa L.) genotypes by zinc fertilization - Muhammad Jan; Muhammad Anwar-ul-Haq; Adnan Noor Shah; Muhammad Yousaf; Javaid Iqbal; Xiuling Li; Depeng Wang; Shah Fahad (Arabian Journal of Geosciences, 2019)

First detection and molecular characterization of avian polyomavirus in young parrots in Pakistan - Aayesha Riaz; Arfan Yousaf; Muhammad Moaeen-ud-Din; Muhammad Ali Abdullah Shah; Tayyaba Zainab; Sadia Masood; Naeem Akhter; Adnan Ali (Veterinary Research Communications, 2019)

Divisional disparities on climate change adaptation and mitigation in Punjab, Pakistan: local perceptions, vulnerabilities, and policy implications - Mudassar Hussain; Abdul Rahman Butt; Faiza Uzma; Rafay Ahmed; Abdul Rehman; Muhammad Ubaid Ali; Habib Ullah; Balal Yousaf (Environmental Science and Pollution Research, 2019)

Zinc biofortification of cereals—role of phosphorus and other impediments in alkaline calcareous soils - Muhammad Akhtar; Sundas Yousaf; Nadeem Sarwar; Saddam Hussain (Environmental Geochemistry and Health, 2019)

Saudi Arabia-China-Pakistan Economic Corridor: intergovernmental green initiatives - Asma Naz; Khalid Zaman; Sheikh Usman Yousaf; Abdelmohsen A. Nassani; Abdullah Mohammed Aldakhil; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2019)

Investigating the drinking and surface water quality and associated health risks in a semi-arid multi-industrial metropolis (Faisalabad), Pakistan - Yusra Mahfooz; Abdullah Yasar; Muhammad Tayyab Sohail; Amtul Bari Tabinda; Rizwan Rasheed; Samina Irshad; Balal Yousaf (Environmental Science and Pollution Research, 2019)

A systematic review on global pollution status of particulate matter-associated potential toxic elements and health perspectives in urban environment - Muhammad Ubaid Ali; Guijian Liu; Balal Yousaf; Habib Ullah; Qumber Abbas; Mehr Ahmad Mujtaba Munir (Environmental Geochemistry and Health, 2019)

Ranking renewable energy production methods based on economic and environmental criteria using multi-criteria decision analysis - Muhammad Razi; Yousaf Ali (Environment Systems and Decisions, 2019)

A comprehensive review on environmental transformation of selenium: recent advances and research perspectives - Habib Ullah; Guijian Liu; Balal Yousaf; Muhammad Ubaid Ali; Samina Irshad; Qumber Abbas; Rafay Ahmad (Environmental Geochemistry and Health, 2019)

Seismic vulnerability of non-ductile RC buildings in Pakistan through stochastic analysis of design/construction deficiencies - Muhammad Usman Ali; Shaukat Ali Khan; Muhammad Yousaf Anwar; Uzair Maqbool (Bulletin of Earthquake Engineering, 2019)

Ecophysiological response of early stage Albizia lebbeck to cadmium toxicity and biochar addition - Muhammad Talha Bin Yousaf; Muhammad Farrakh Nawaz; Hammad Fayyaz Khawaja; Sadaf Gul; Shafaqat Ali; Irfan Ahmad; Fahd Rasul; Muhammad Rizwan (Arabian Journal of Geosciences, 2019)

Deadly outbreak of chickenpox at district Faisalabad, Pakistan: possible causes, and preventive way forward - Muhammad Zubair Yousaf; Sadia Zia; Khalid Mahmood Anjum; Usman Ali Ashfaq; Muhammad Imran; Samia Afzal; Muhammad Sarfaraz Iqbal (Molecular Biology Reports, 2018)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Identification of phytotoxins in different plant parts of Brassica napus and their influence on mung bean - Azhar Mehmood; Muhammad Naeem; Farhan Khalid; Yousaf Saeed; Tasawer Abbas; Khawar Jabran; Muhammad Aqeel Sarwar; Asif Tanveer; Muhammad Mansoor Javaid (Environmental Science and Pollution Research, 2018)

Effects of selected synthetic insecticides on the total and differential populations of circulating haemocytes in adults of the red cotton stainer bug Dysdercus koenigii (Fabricius) (Hemiptera: Pyrrhocoridae) - Zahid Mahmood Sarwar; Mamuna Ijaz; Muhammad Altaf Sabri; Hasnain Yousaf; Muhammad Mohsan (Environmental Science and Pollution Research, 2018)

Nonlinear time series modeling and forecasting the seismic data of the Hindu Kush region - Muhammad Yousaf Khan; Stefan Mittnik (Journal of Seismology, 2018)

Evaluating the health risks of potentially toxic elements through wheat consumption in multi-industrial metropolis of Faisalabad, Pakistan - Qumber Abbas; Balal Yousaf; Guijian Liu; Muhammad Zia-ur-Rehman; Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Syed Arif Hussain (Environmental Science and Pollution Research, 2017)

Erratum to: Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Association of chili leaf curl betasatellite with tomato leaf curl disease - Muhammad Qasim Aslam; Khalid P. Akhtar; Mohy-u-Din Akram; Muhammad Y. Saleem; Nighat Sarwar; Sumaira Yousaf (Journal of General Plant Pathology, 2017)

Nitrogen fertilization and conservation tillage: a review on growth, yield, and greenhouse gas emissions in cotton - Adnan Noor Shah; Javaid Iqbal; Mohsin Tanveer; Guozheng Yang; Waseem Hassan; Shah Fahad; Muhammad Yousaf; Yingying Wu (Environmental Science and Pollution Research, 2017)

Bioavailability evaluation, uptake of heavy metals and potential health risks via dietary exposure in urban-industrial areas - Balal Yousaf; Guijian Liu; Ruwei Wang; Muhammad Imtiaz; Muhammad Zia-ur-Rehman; Mehr Ahmed Mujtaba Munir; Zhiyuan Niu (Environmental Science and Pollution Research, 2016)

Atmospheric emission of nitric oxide and processes involved in its biogeochemical transformation in terrestrial environment - Awais Shakoor; Muhammad Abdullah; Balal Yousaf; Amina; Youhua Ma (Environmental Science and Pollution Research, 2016)

Comparison of antioxidant enzyme activities and DNA damage in chickpea (Cicer arietinum L.) genotypes exposed to vanadium - Muhammad Imtiaz; Muhammad Adnan Mushtaq; Muhammad Shahid Rizwan; Muhammad Saleem Arif; Balal Yousaf; Muhammad Ashraf; Xiong Shuanglian; Muhammad Rizwan; Sajid Mehmood; Shuxin Tu (Environmental Science and Pollution Research, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

Bisphenol A exposure and healing effects of Adiantum capillus-veneris L. plant extract (APE) in bisphenol A-induced reproductive toxicity in albino rats - Balal Yousaf; Amina; Guijian Liu; Ruwei Wang; Abdul Qadir; Muhammad Ubaid Ali; Qudsia Kanwal; Bushra Munir; Asmatullah; Zaigham Abbas (Environmental Science and Pollution Research, 2016)

Structural styles, hydrocarbon prospects, and potential in the Salt Range and Potwar Plateau, north Pakistan - Ishtiaq A. K. Jadoon; Matthias Hinderer; Beenish Wazir; Rizwan Yousaf; Sher Bahadar; Muhammad Hassan; Zeeshan-ul-Hassan Abbasi; Sidra Jadoon (Arabian Journal of Geosciences, 2015)

The endophyte Enterobacter sp. FD17: a maize growth enhancer selected based on rigorous testing of plant beneficial traits and colonization characteristics - Muhammad Naveed; Birgit Mitter; Sohail Yousaf; Milica Pastar; Muhammad Afzal; Angela Sessitsch (Biology and Fertility of Soils, 2014)